C-hexaphenyl-substituted trianglamine as a chiral solvating agent for carboxylic acids - Gualandi, Andrea; Grilli, Stefano; Savoia, Diego; Kwit, Marcin; Gawroński, Jacek (Organic & biomolecular chemistry, 2011)
Chiral hexaazamacrocycles with a trianglamine structure and C(3)-symmetry, containing six ring substituents and twelve stereocenters have been tested as chiral solvating agents (CSAs) for α-substituted carboxylic acids. Excellent results have been obtained with a hexaphenyl-substituted macrocycle. The optimal ratio between the macrocycle and racemic acid, allowing for baseline separation of the enantiomers' signals in the (1)H NMR spectrum, was dependent on the type of acid, in particular on its degree of acidity. The analyte and the CSA could be separated and recovered by a simple acid-base extraction and reused without purification. The conformations of the free and protonated hexaamino macrocycles were inferred by CD spectroscopic studies and DFT calculations.